Effective Killing of Acute Myeloid Leukemia by TIM-3 Targeted Chimeric Antigen Receptor T Cells - Lee, Wen-Hsin Sandy; Ye, Zhiyong; Cheung, Alice M.S.; Goh, Y.P. Sharon; Oh, Hsueh Ling Janice; Rajarethinam, Ravisankar; Yeo, Siok Ping; Soh, Mun Kuen; Chan, Esther Hian Li; Tan, Lip Kun; Tan, Soo-Yong; Chuah, Charles; et al. (Molecular cancer therapeutics, 2021)
Acute myeloid leukemia (AML) is an aggressive disease with poor outcomes, overwhelmingly due to relapse. Minimal residual disease (MRD), defined as the persistence of leukemic cells after chemotherapy treatment, is thought to be the major cause of relapse. The origins of relapse in AML have been traced to rare therapy-resistant leukemic stem cells (LSCs) that are already present at diagnosis. Effective treatment strategies for long-term remission are lacking, as it has been difficult to eliminate LSCs with conventional therapy. Here, we proposed a new approach based on the chimeric antigen receptor (CAR)-directed T lymphocytes, targeting T-cell immunoglobulin, and mucin domain 3 (TIM-3) to treat MRD in patients with AML. TIM-3 is selected as the target because it is highly expressed on AML blasts and LSCs in most subtypes regardless of the patient's genetic characteristics and treatment course. Moreover, it is absent in the normal hematopoietic stem cells, granulocytes, naïve lymphocytes, and most normal nonhematopoietic tissues. Using a naïve human Fab phage display library, we isolated an anti-human TIM-3 antibody and designed a second-generation anti–TIM-3. Our anti–TIM-3 CAR T cells exhibit potent antileukemic activity against AML cell lines and primary AML blasts, and in the mouse models. More importantly, we demonstrate efficient killing of the primary LSCs directly isolated from the patients. Hence, eradication of the LSCs present in the MRD by anti–TIM-3 CAR T-cell therapy following the first-line treatment may improve the clinical outcomes of patients with AML.